Supply chain and logistics in national, international and governmental environment : concepts and models - Zanjirani Farahani, Reza; Asgari, Nasrin; Davarzani, Hoda (Contributions to management science., 2009)
The main concern of this book are national and governmental supply chains, which have rarely been considered by regular publications in related disciplines. Not only are readers provided with useful information about the latest topics in supply chains; the book also helps them to track the history and related cases of each topic. This manuscript has been organized in twelve chapters, so that readers can study each chapter not only dependently but also independently. If someone wants to study the book more in-depth, the suggested sequencing in the preface can be helpful. Generally, the readers of this book can be divided into at least two groups: 1) students studying for a master degree, who can use this book in their courses as a whole, 2) experts who want to learn more about a new topic in logistics and supply chain management; this group may want to read a short chapter about a specific topic in this book.- Resumé vydavatel